Impact of Cold Atmospheric Plasma Jet Treatment on the Physicochemical Properties of Surface Water - Baniya, Hom Bahadur; Dhungana, Santosh; Singh, Akhilesh Kumar; Subedi, Sabina; Kaucha, Nisha; Guragain, Rajesh Prakash (Journal of Institute of Science and Technology, 2025)
Cold atmospheric plasma jet (CAPJ) is a rapidly emerging multidisciplinary research field that stands out for its chemical-free and eco-friendly characteristics. It has garnered notable interest in recent years owing to its vast potential applications across various domains. One of its intriguing applications is in the treatment of water. Plasma transforms water into an acidic environment, leading to alterations in several key properties, including redox potential, electrical conductivity, dissolved solids, pH, and turbidity. Water treated with plasma, due to its distinct chemical composition compared to regular water, offers a promising alternative for microbial disinfection. In this research, CAPJ is generated using high voltage power supply (5 kV, 20 kHz) at standard atmospheric conditions and room temperature in an argon environment. The discharge generated by this system is thoroughly characterized using electrical and optical methods. Water sample collected from tap and well are treated with cold plasma jet and their physiochemical properties have been characterized.